HIV/AIDS in South African schools: Neuropsychological and psychoeducational implications. Issue 4 (1st October 2020) - Cockcroft, Kate; Cassimjee, Nafisa
ABSTRACT: In this article, we briefly describe the current epidemiology of HIV/AIDS among South African schoolchildren, as well as the neurocognitive, academic and psychosocial difficulties they experience. Cultural factors linked to HIV prevention and treatment are identified, and government and schools' response to HIV/AIDS is outlined. We then evaluate what has been done thus far to address these issues in the educational, healthcare, and government contexts. In conclusion, we point to recommendations for how school psychologists and other school-based professionals can work with affected children, families, communities, agencies and governments to effect change.